Кон Iris Marion Young, On Female Body Experience: “Throwing Like a Girl” and Other Essays: Për Iris Marion Young, On Female Body Experience: “Throwing Like a Girl” and Other Essays - Ivanovska, Marija; Ahmeti, Xhabir (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Marija Ivanovska | Марија Ивановска Title (Macedonian): Кон Iris Marion Young, On Female Body Experience: “Throwing Like a Girl” and Other Essays Title (Albanian): Për Iris Marion Young, On Female Body Experience: “Throwing Like a Girl” and Other Essays Translated by (Macedonian to Albanian): Xhabir Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 221-225 Page Count: 5 Citation (Macedonian): Марија Ивановска, „Кон Iris Marion Young, On Female Body Experience: “Throwing Like a Girl” and Other Essays“, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 221-225. Citation (Albanian): Marija Ivanovska, „Për Iris Marion Young, On Female Body Experience: “Throwing Like a Girl” and Other Essays“, përkthim nga Maqedonishtja Xhabir Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 221-225.